If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) = 7x + -10x + 1 Reorder the terms: 3(6 + x) = 7x + -10x + 1 (6 * 3 + x * 3) = 7x + -10x + 1 (18 + 3x) = 7x + -10x + 1 Reorder the terms: 18 + 3x = 1 + 7x + -10x Combine like terms: 7x + -10x = -3x 18 + 3x = 1 + -3x Solving 18 + 3x = 1 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 18 + 3x + 3x = 1 + -3x + 3x Combine like terms: 3x + 3x = 6x 18 + 6x = 1 + -3x + 3x Combine like terms: -3x + 3x = 0 18 + 6x = 1 + 0 18 + 6x = 1 Add '-18' to each side of the equation. 18 + -18 + 6x = 1 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = 1 + -18 6x = 1 + -18 Combine like terms: 1 + -18 = -17 6x = -17 Divide each side by '6'. x = -2.833333333 Simplifying x = -2.833333333
| 1/3r+1/5r=8 | | .25(-8+8x)=-2+2x | | -3w+4-w-17= | | 6x-1=-3x+13 | | 5(-x+9)-8=-19 | | 72=4x+4(-3x+2) | | -8=-(x+10) | | 6(n+8)=5(n+-4) | | 0.5+6.0y=8.0 | | 8y+4(2+y)=3(y-5)+10y | | 4x+5=-1/3x-8 | | 4x-153=47-6x | | 4/5(x-8)=-12 | | 18=b+3+4b | | x(4x-3)=(4x+6)(x-3) | | (2x-y)(4x^2+2xy+y^2)= | | -32+4x=9x+13 | | 16x+12=93 | | 1/7(x+2)=6 | | -6x-59=3x+121 | | 5x=4(-.33+x)+8 | | 13x+97=-14x+1+15x | | 64s^2-144sf+81f^2= | | 30-5(p-10)=1p | | -23-x=2x+10 | | 5(-6+6x)=-5x+30 | | 3x-(4x+3)=4x-28 | | 5(x+-6)=-5x+30 | | -9x-25=38-6x | | u+2=10 | | 2(2+2x)=3(x-5) | | 9-5x+=4-5x |